Analyzing the implementation of health information systems to improve service efficiency in community health centers - Muh Ihsan Kamaruddin; A. Syamsinar Asmi; Wa Ode Novi Angraeni; Wahyudi Hardi; Jessy Andre Mangaya Takke (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: The increasing demand for efficient, accurate, and integrated health services in primary care underscores the essential role of Health Information Systems (HIS) in Puskesmas. Despite national policies encouraging digital transformation, many Puskesmas still face challenges, including limited infrastructure, inadequate digital literacy among health workers, and fragmented system integration. This study aims to analyze the implementation of HIS in Puskesmas, assess its contribution to service efficiency, and identify supporting and inhibiting factors that influence system adoption. Methods: The study employs a qualitative case-study approach involving several Puskesmas that have implemented HIS. Data were collected through in-depth interviews with health workers and administrative staff, direct observations of HIS use in daily operations, and document analysis related to system policies and operational procedures. The qualitative data were analysed through thematic coding and triangulation across sources to ensure validity and reliability. Results: The findings reveal that HIS significantly supports faster patient data processing, improves the accuracy of medical records, and reduces administrative burdens. However, system effectiveness varies across facilities depending on infrastructure readiness, staff competency, and leadership support. Barriers such as insufficient training, inconsistent internet connectivity, and inadequate system maintenance hinder optimal utilisation. Conversely, strong managerial commitment, user-friendly system design, and continuous government support emerge as key enablers. Conclusion: This study concludes that the implementation of HIS has the potential to substantially enhance service efficiency in Puskesmas when supported by adequate resources and policy alignment. Recommendations include strengthening digital literacy training, improving infrastructure, ensuring continuous technical support, and developing adaptive policies to sustain long-term HIS utilization.